Pengaruh Terapi Relaksasi Progresif terhadap Penurunan Tingkat Kecemasan dalam Menghadapi Uji Kompetensi Mahasiswa Tingkat III Akper Muhammadiyah Cirebon - Hidayat, Eyet (Jurusan Keperawatan FIKES UNSOED, 2017)
A nurse is deemed competent to have a competency certificate obtained through a competency test. Anggraeni Novi (2013): 3rd grader D III Nursing Universitas Pendidikan Indonesia 56% experience anxiety from mild to moderate level in facing competency test. There is an effect of progressive muscle relaxation on anxiety levels in schizophrenic patients in RSJ Bali Province (Laksmi, 2015). This study aims to determine the effect of progressive relaxation therapy to decrease the level of anxiety in the face of nurse competence test at the level III student AKPER Muhammadiyah Cirebon. The study design used